A SIMULATION-MODEL FOR DETERMINING MAINTENANCE STAFFING IN AN INDUSTRIAL-ENVIRONMENT - Duffuaa, S. O. (2020)
In a plant, the size of a maintenance staff must be related to the level of output.The optimal level of maintenance is essential for maximizing the output of the production process.This paper develops a simulation model to determine the size of a maintenance crew.The heart of the simulation model is the machine servicing model.The model is applied to a local soft drink plant to determine the optimal number of their maintenance crew, and the result of the study is presented.